Nød og neppe Fra anrop til beslutning ved politiets operasjonssentral - Lundgaard, Jenny Maria (Scandinavian University Press (Universitetsforlaget), 2021)
In police control rooms, everyday life is unpredictable. When handling a call, the staff must make assessments and important decisions based on limited information and often under time pressure: Which calls should become patrol work, and which should not?This book is a study of the work of police control rooms. It is based on extensive ethnographic fieldwork, and explores the field based on perspectives from actor-network theory, critical security studies, police science, and criminology. The book looks at the conditions for, significance of, and dilemmas in the control room's work, and further explores categorization practices, information processing, goal management, the relationship between the control room and the patrols, professionalization, and emergency preparedness work.The book's analysis has implications not only for control rooms, but also for our understanding of the operational police work as a whole and for the conditions and significance of this work.